1970
DOI: 10.3126/jpn.v1i1.4446
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in chronic kidney disease patients in predialysis and postdialysis stages

Abstract: Background: Chronic kidney disease is usually associated with anemia and the level of anemia correlates with the severity of renal failure. This study was carried out to evaluate the profile of anemia and to find the correlation between the severity of anemia and serum creatinine levels in predialysis and postdialysis Chronic kidney disease patients. Materials and Methods: A cross-sectional study was conducted in 40 chronic kidney disease patients in the department of pathology and nephrology, KIST Medical Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
4
12
1
Order By: Relevance
“…Inflammation caused by the dialytic membrane can lead to lower mean Hb and Hct levels in dialysis patients. 9 Our study showed significant patients, which is similar to the study done by Seuga et al 10 The degree of anaemia increases as progressive destruction of kidney tissue occurs. This study like others revealed presence of a predominantly moderate degree of anaemia in pre-and post-dialysis patients.…”
Section: Discussionsupporting
confidence: 91%
“…Inflammation caused by the dialytic membrane can lead to lower mean Hb and Hct levels in dialysis patients. 9 Our study showed significant patients, which is similar to the study done by Seuga et al 10 The degree of anaemia increases as progressive destruction of kidney tissue occurs. This study like others revealed presence of a predominantly moderate degree of anaemia in pre-and post-dialysis patients.…”
Section: Discussionsupporting
confidence: 91%
“…The nding of this study is also very different from the Dialysis Outcomes and Practice Patterns study (DOPPS) international study, which reported a range of anemia prevalence from 23-77% in the studied countries [10]. However the present study is in agreement with the nding of earlier studies which found anemia in all studied patients [19]. It does also identify a greater prevalence of anemia in African descent patients that is inconsistent with the 67.5% found by a Brazilian study [20].…”
Section: Discussionsupporting
confidence: 59%
“…Urinary protein:creatinine ratio was found to not correlate with either HGB or HCT. A lack of correlation between creatinine concentration and the severity of anemia has been documented in human studies; 28 it has been proposed to result from the insensitivity of blood creatinine in detecting a decline in glomerular filtration rate (GFR), arising from changes in both the metabolism and renal handling of creatinine, and from compensatory mechanisms that serve to maintain normal GFR despite a reduction in functional renal mass. 27,29 There was also a correlation between the increase in blood pressure and decline in HGB and HCT, although not as strong as that seen for plasma urea.…”
Section: Discussionmentioning
confidence: 99%